Evaluación del extracto de Jengibre (Zingiber Officinale), sobre los índices productivos en pollos de engorde - Torres Basurto, Odalis Damaris (2024)
The purpose of this research was to evaluate the effect of three levels of inclusion of Zingiber officinale (ginger) extract in the drinking water as a growth promoter in the diet of broiler chickens along with the productive parameters and the cost/benefit per treatment. The chickens were assigned to 4 treatments; T0-(control treatment ), T1 - (4ml of Ginger addition) T2 - (8ml % of Ginger addition), T3 - (12ml of Ginger addition) was used A Completely Randomized Design (DCA) occurred after the first two weeks of life, that is, the application began from day 16 to day 42, with 160 chickens that were evaluated by applying these treatments, it was possible to show result in week 6 food consumption was similar between treatments, with T1 being the highest (5291.05 g). Treatment T3 showed the greatest weight gain, reaching the highest weight at the end of the study (3142.58 g). T3 had the best feed efficiency in week 6 (1.67).In terms of growth and body weight in chickens, treatment T3 showed the greatest increase in the weight of chickens, reaching the highest weight at the end of the period (3142.58 g). T2 achieved the greatest weight gain in weeks six (795.84) showed better weight gain and feed conversion. In conclusion, the addition of Zingiber officinale extract to the diet of chickens showed a statistically significant difference in terms of weight gain and feed conversion during the 42-day study.